PEMIKIRAN PRAGMATISME IBNU KHALDUN DAN RELEVANSINYA DENGAN MERDEKA BELAJAR KURIKULUM MERDEKA - Mohammad Firmansyah; Asmuki Asmuki (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
Link and match as posterity educational project. This project aims to connect the knowledge in schools with the citizen needs. In Islamic literature mentioned that Ibn Khaldun is an influential Muslim figure. The Muqaddimah book which written became a media for his brilliant ideas in the society social order, including educational practices. Through a literature review of Ibn Khaldun's thoughts used in books and journal articles using text and context analysis techniques, it can be interpreted that Ibn Khaldun's pragmatism-instrumental thinking has relevance to independent learning in the independent curriculum (MBKM) in Indonesia. The mean of relevance in the al-Hiwar method to realize students get additional insight of knowledge through the integration of subject matter and theory obtained in class with practical experience outside the classroom and the surrounding community.